An Examination of the Necessary Adjective: Decolonising “African” Philosophy - May, Joshua (The Stellenbosch Socratic Journal, 2023)
This paper engages in the decolonisation of African philosophy through a critical examination of necessary adjectives and their implications on global philosophy. I contend that decolonising African philosophy necessitates a transformative process that challenges the dominance of "Western" philosophy and dismantles the power dynamics perpetuated by necessary adjectives. By recognising the inherent problems within the discipline, engaging with diverse perspectives, and de-emphasising restrictive borders, philosophy can evolve into a more inclusive, equitable, and globally interconnected field of knowledge. By exploring discrepancies in usage of necessary adjectives between ‘Western’ and ‘non-Western’ philosophies, I uncover underlying assumptions and systemic devaluations inherent in these linguistic constructs. I argue that necessary adjectives are rooted in colonial logic which perpetuates racial hierarchies and systematically marginalises ‘non-Western’ philosophies. Necessary adjectives construct a binary framework in which Western philosophy is presented as normative and universal, whilst othered philosophies are relegated to the margins, requiring Western validation. This restricts diversity of thought and limits the scope of global philosophical discourse. Thus, in order to decolonise African philosophy, I argue for deeper engagement with the problematic nature of necessary adjectives. I advocate for the deconstruction of the Western perspective and its underpinnings in white supremacy, whilst emphasising the contextual situatedness of philosophies. By problematising “Western” philosophy, acknowledging its arbitrary nature, exclusionary practices, and its rewriting of history, I suggest a path towards decolonisation that encompasses inclusion of marginalised voices and a reimagining of both philosophy education in Africa, and of the borders between philosophies.